Cover Picture: Silyl Chalconium Ions: Synthesis, Structure and Application in Hydrodefluorination Reactions (Chem. Eur. J. 42/2017). Issue 42 (7th June 2017) - Kordts, Natalie; Künzler, Sandra; Rathjen, Saskia; Sieling, Thorben; Großekappenberg, Henning; Schmidtmann, Marc; Müller, Thomas
Abstract : Silylated chalconium ions based on peri ‐naphthalene and acenaphthene scaffolds are synthesized and introduced as versatile amphiphilic reagents. The investigation of their spectroscopic, structural and bonding properties revealed that their silyl Lewis acidity is controlled by the nature of the chalcogen donor and by the carbon backbone. This opens the perspective for an effective fine tuning and control of their reactivity. Their use as amphiphilic CATalyst was exemplarily demonstrated in hydrodefluorination reactions. More information can be found in the Full Paper by T. Müller et al. onpage 10068 .